The Effect of Good Corporate Governance Characteristics on Carbon Emission Disclosure in Carbon Intensive Industry - Ni Putu Puspita Sari; Robith Hudaya (Cita Konsultindo Research Center, 2023)
This study examines the effect of good corporate governance characteristics, namely managerial ownership, institutional ownership, environmental committee, board size, independent commissioners, gender diversity, and CEO duality, on carbon emissions disclosure. This study used a quantitative approach, utilizing secondary data sourced from annual reports and sustainability reports from the energy, industry, materials, and transportation sectors. The sample observation period in this study is from 2018 - 2022. The sampling method uses purposive sampling to obtain a final sample of 26 companies. The selection of analytical technique involves panel data regression analysis utilizing the selected random effect model. The analytical tool used in this purpose is Eviews 12. The findings of this study indicate that variables such as management ownership, institutional ownership, board size, independent commissioners, and gender diversity did not have a significant effect on carbon emissions disclosure. Furthermore, the presence of environmental committees and the practice of CEO duality were found to have a significant positive effect on the disclosure of carbon emissions. Also, the findings of this study indicate that the effect of firm size on the relationship between good corporate governance characteristics and carbon emission disclosure is limited to that of a predictor rather than a mediator.